2009
DOI: 10.1111/j.1747-4949.2009.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Blood Pressure Circadian Rhythm in Acute Ischaemic Stroke: are Lacunar Strokes Really Different?

Abstract: Our results show clear differences in the blood pressure circadian rhythm of acute ischaemic stroke between lacunar and nonlacunar infarctions by means of 24-h blood pressure monitoring. The magnitude of nocturnal systolic and diastolic blood pressure dip was significantly higher in lacunar strokes. Besides, patients with lacunar strokes presented a higher percentage of dipping patterns in the diastolic blood pressure circadian rhythm. Therefore, one should consider the ischaemic stroke subtype when deciding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
22
0
3
Order By: Relevance
“…There was no long-term follow-up. 3,[20][21][22][23][24][25] In the present study, we examined very old patients with acute stroke and used both admission casual BP levels and 24H BPM. Previous studies have demonstrated contradictory results regarding the effect of admission BP levels on outcomes in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no long-term follow-up. 3,[20][21][22][23][24][25] In the present study, we examined very old patients with acute stroke and used both admission casual BP levels and 24H BPM. Previous studies have demonstrated contradictory results regarding the effect of admission BP levels on outcomes in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated contradictory results regarding the effect of admission BP levels on outcomes in patients with acute stroke. 5,13,14,[19][20][21][22][23][24][25][26] All studies evaluated a short-term (maximum 6 months) outcome. We did not observe any effect of admission BP levels on short-or long-term outcome, which may be related to the older age of our study group or to the fact that admission BP did not represent true BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lacunar strokes tend to show this secondary worsening of stroke symptoms more often than patients with cortical strokes [1]. A hypothesis is that some stroke patients, mainly with lacunar stroke and premorbid hypertension, show extreme nocturnal blood pressure falls or just no nocturnal blood pressure falls at all [1,2,4,9,10]. Nocturnal blood pressure falls of 10-15 mmHg are physiological.…”
Section: Introductionmentioning
confidence: 97%
“…Vascular risk factors of LS and NLS relate directly to the underlying etiologies of the two subtypes (Kazui et al, 2000;Khan et al, 2012;Park et al, 2012). However, relatively little is known of the non-vascular risk factors contributing to ischemic stroke (Petty et al, 2000;Cokar et al, 2008;Prodan et al, 2008;Castilla-Guerra et al, 2009;Jackson et al, 2010;Zhang et al, 2011). Identifying the risk factors of ischemic stroke and the determinants of outcome (stroke recurrence and mortality) after onset of stroke is the basis for stroke prevention strategies.…”
Section: Introductionmentioning
confidence: 99%